Analysis of The Influence of Work Environment, Work Motivation, Work Discipline on Job Satisfaction and Employee Performance (Case Study at the Regional Secretariat of Ponorogo Regency) - Wahyu Dwi Kuncoro; Riawan Riawan (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to analyze the influence of a comfortable and safe work environment and the existence of motivation and discipline can increase job satisfaction so that it can increase effective work productivity to employee performance". Design/Approach: "This study applies a quantitative approach using primary data maps from 40 respondents from employees of the Ponorogo Regency Regional Secretariat. The sampling technique in this study is non-probability sampling using the purposive sampling method". Findings: "The results of this study show that a good work environment can increase employee comfort and satisfaction when they do their jobs. Employees with high work motivation are more enthusiastic and focused in carrying out their responsibilities. Work discipline also has a positive and significant effect on employee job satisfaction. Good discipline creates regularity in work, which increases employee satisfaction and improves their performance. Employees who are satisfied with their work environment, discipline, and motivation tend to be more productive and qualified. In addition, work discipline, work motivation, and work environment have a positive effect on employee performance through job satisfaction". Originality: "This research focuses on how to manage a good work environment in employees of the Regional Secretariat of Ponorogo Regency, this study has analyzed the influence of the work environment affecting job satisfaction, work motivation affecting job satisfaction and work discipline affecting performance, and with job satisfaction can increase productivity in employee performance so that it can make performance more efficient.